Noninvasive ratiometric fluorescence imaging of γ-glutamyltransferase activity using an activatable probe. Issue 6 (22nd January 2021) - Huang, Zheng; An, Ruibing; Wei, Shixuan; Wang, Jinfang; Ye, Deju
Abstract : A ratiometric fluorescent probe constructed by covalently linking an 'always-on' BODIPY fluorophore with a GGT-activatable near-infrared (NIR) fluorescent substrate was reported for real-time imaging of GGT activity in living cells and in vivo . Abstract : γ-Glutamyltranspeptidase (GGT) is an important aminopeptidase overexpressed in many malignant tumors, and accurate detection of its activity is useful for the diagnosis and treatment of tumors. Herein, we report a GGT-activatable ratiometric fluorescent probe (1 ) constructed by covalently linking an 'always-on' BODIPY fluorophore with a GGT-activatable near-infrared (NIR) fluorescent substrate. Upon interaction with GGT, the NIR fluorescence at 735 nm in probe 1 is significantly enhanced, while the fluorescence of BODIPY at 517 nm remains unchanged. Using BODIPY fluorescence as an internal standard, significantly enhanced ratiometric fluorescence between 735 nm and 517 nm could be achieved, allowing accurate detection of the activity of GGT in living subjects independent of probe concentration. We demonstrate that probe 1 is feasible for the evaluation of GGT levels in different tumor cells and differentiation of GGT-positive tumor cells from GGT-negative normal tissue cells. Moreover, probe 1 is further applied for the visualization of tumor via noninvasive ratiometric fluorescence imaging of GGT activity, which could facilitate the detection of GGT-positive tumor tissues and study of GGT-related pathological processes.